Characterization Of Nano-Silica Material as An Insulating Brick for Enhancing Thermal Comfort in Buildings - Wan Amizah Wan Jusoh; Loke, Kok Foong; Syed Zin, Syed Mohd Fareed; Nurul Hidayah Roslan; Mahmudin, Muhammad Faheem (Journal of Advanced Industrial Technology and Application, 2024)
The study investigates the application of nano-silica as a thermal insulating material in brick construction, aiming to improve building thermal comfort. Nano-silica, recognized for its thermal resistance and mechanical stability, was incorporated in varying proportions into cement bricks to evaluate its influence on the physical, mechanical, and thermal properties of the resulting bricks. A total of 60 samples were prepared and subjected to water absorption, density, ultrasonic pulse velocity, compressive strength, and thermal conductivity tests. The results indicate a positive correlation between nano-silica content and improved thermal insulation, though excessive nano-silica led to a decrease in compressive strength due to particle agglomeration. The optimal nano-silica content, 5%, provided a balance, enhancing thermal insulation without compromising structural integrity. The findings suggest that nano-silica bricks offer potential as a sustainable construction material, aligning with energy efficiency goals in building design. Further research is recommended to optimize nano-silica content for practical applications in varied climatic conditions.